2018
DOI: 10.1016/j.jinsphys.2018.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular activity of NBAD-synthase is responsible for colouration of brown spots in Ceratitis capitata wings

Abstract: After the emergence of the Ceratitis capitata imago, the pale and folded wings are expanded and sclerotized to acquire the definitive form and to stabilize the cuticle. The wings of this fly show a specific pattern of brownish and black spots. Black spots are pigmented by melanin, whereas there was scarce information about the development of the brownish spots. N-beta-alanydopamine (NBAD) is the main tanning precursor in C. capitata body cuticle, and we hypothesized that it may be responsible for the colourati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 34 publications
(34 reference statements)
1
2
0
Order By: Relevance
“…Our studies complement previously published studies ( Perez et al., 2018 ) describing the tanning process in the wings of newly emerged adults of C. capitata . First, the increased activity of NBAD synthase in the body temporarily coincided with the definitive tanning of the head, thorax, and abdominal cuticles and coincided with the acquisition of a definitive body shape (2 h after adult emergence).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our studies complement previously published studies ( Perez et al., 2018 ) describing the tanning process in the wings of newly emerged adults of C. capitata . First, the increased activity of NBAD synthase in the body temporarily coincided with the definitive tanning of the head, thorax, and abdominal cuticles and coincided with the acquisition of a definitive body shape (2 h after adult emergence).…”
Section: Discussionsupporting
confidence: 90%
“…One hour after ecdysis in adults, the characteristic brown and black spots of Ceratitis began to be recognized. However, the definitive pattern of colouration is attained 24 h after emergence ( Perez et al., 2018 ). Our results indicate that while the shape of the body and the final position of the wings would be reached within the first two hours after emergence, the final colouration of the wings was completed after 24 hours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of Ebony in the pigmentation of C . capitata wings was investigated by Pérez et al 49 . Using biochemical assays, the authors showed that Ebony is spatially pre-patterned in the yellowish-brown bands of the medfly wings during early adult development, maintaining an extracellular activity long after epithelial cells disappear from the lamina.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism behind this effect is unclear, but it seems to follow a phylogenetic pattern and therefore could be related to a species-specific distribution of pigment precursors through their wing veins. The role of Ebony in the pigmentation of C. capitata wings was investigated by Pérez et al 49 . Using biochemical assays, the authors showed that Ebony is spatially pre-patterned in the yellowish-brown bands of the medfly wings during early adult development, maintaining an extracellular activity long after epithelial cells disappear from the lamina.…”
Section: Contributions Of Ebony To Wing Pigmentationmentioning
confidence: 99%